Impact assessment caused by bradyseism phenomena in the Campi Flegrei area - Perelli, Francesca Linda; Di Maio, Luigia Sara; De Gregorio, Daniela; Magliulo, Gennaro; De Martino, Prospero; Zuccaro, Giulio (Frontiers in Built Environment, 2023)
Campi Flegrei (Italy) is among the areas with the greatest volcanic explosive risk in the world due to the dangerousness of the expected hazards, the high exposed value (about 500,000 people will be evacuated during the “alarm phase”), and the vulnerability of the urban settlements under the effect of the volcanic phenomena. The last two dramatic bradyseism phases occurred in 1969–1972 and 1982–1984 when Pozzuoli town was affected by rapid ground inflation, which brought an overall higher level of about 3.5 m and caused numerous earthquakes (M ≤ 4.2), with severe damage to buildings. During 1984, the seismicity was intense, with 33 events with 0.5 < M ≤ 3 and six with 3 < M ≤ 3.8. Subsequently, the Campi Flegrei caldera was characterized by general subsidence for about 20 years until 2005, when a new inflation period started and is still ongoing (∼1 m). The areal distribution of the recent uplift is characterized by the maximum vertical displacement in the town of Pozzuoli, with a radial decrease from the caldera center outwards. The need to better understand Campi Flegrei volcanic activity is fundamental to protecting the population from hazards linked to explosive volcanic eruptions and understanding the role of seismicity as a possible precursor of a potential eruption. In this perspective, as part of the activities of the PLINIVS Study Centre (Centre of Competence of Italian Civil Protection Department for Volcanic Risk), the authors developed a procedure, implemented in a web application, that relates the monitoring of the ground deformation with the behavior of buildings to evaluate the level of progressive damage to the ordinary Phlegraean buildings due to bradyseism in near real time. This study describes the models adopted for the three impact/risk factors (hazard, exposure, and vulnerability) used to estimate building damage.